HUMANITY IN FLUX; ADAPTING EDUCATION TO CONTEMPORARY CHALLENGES AND NURTURING MODERN MINDS FOR TOMMORROW - Sulubara, Seri Mughni; Abidin, Zainal; Zainuddin, Zulfa; Amrizal, Amrizal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
In this modern era, education faces various challenges that are contemporary in nature, so there is a need for new innovations in dealing with the increasingly dynamic development of the world of education. Learning Management System (LMS) consists of Google Classroom and Zoom Platform. The relevant theory related to the research entitled